FORECASTING DRUG STOCKS AT THE AIR JOMAN SUB-DISTRICT HEALTH CENTER USING THE LEAST SQUARE METHOD - Tuti Maharani; Risnawati; Afdhal (Jurnal Teknik Informatika (Jutif), 2022)
The Air Joman District Health Center is a public health service facility owned by the Asahan district government. One of the health services provided is drug supply services. The pharmacy installation is part of the Air Joman Sub-district Health Center which is specifically assigned to manage drugs for patient needs. In inventory control, the warehouse section of the Air Joman District Health Center is carried out manually, where the number of drugs ordered every month is the same as the number of drugs ordered in previous months. So this causes various kinds of problems. Medicine is one of the supplies in human life just in case someone falls ill. Everyone must have felt sick. For example, headache, cough, runny nose, or fever. To cure or reduce pain, usually immediately take medication. Medicines can be bought anywhere, one of which is at the Puskesmas, so that the puskesmas must meet the drug needs so that people can easily get the drugs they need according to the illness they are suffering from. The demand for the need for an uncertain amount of medicine in each period makes it difficult for officers to estimate the need for drugs in the future. Inaccuracy in determining the time and amount of drugs to be ordered resulted in out of stock and delays in drug orders, so that they could not fulfill patient requests at the time of ordering. Forecasting is nothing new in the industrial world. Many previous studies have been carried out because forecasting is considered to be able to maximize the cost of stocking goods. so that it can predict the stock in the future with a forecasting system using the Least Square method.